Empowering Middle School Students with First Aid Knowledge for Everyday Injuries: A Cross-Cultural Community Engagement Program in Krabi, Thailand - Sitti Syabariyah; Amran Jehsoh (The Indonesian Institute of Science and Technology Research, 2025)
Children and adolescents aged 6 to 15 years are a vulnerable age group prone to injuries due to high curiosity and limited awareness or response to hazards. Data indicate that approximately 42.56% of middle school students experience injuries, ranging from minor to severe. The most common types of injuries include falls, sprains, puncture wounds, lacerations, fractures, bruises, foreign body intrusion, and traffic accidents. The most frequent injury sites are the lower limbs (67.9%), followed by the upper limbs (32.7%) and the head (11.9%). This community service program was designed to equip middle school students at Ekkapap International School, Krabi, Thailand, with essential first aid knowledge for everyday injuries. The theme was selected to provide basic health literacy through practical, interactive, and engaging approaches. The methods included wound illustration, hands-on activities such as wound cleaning, dressing with gauze, applying adhesive bandages, and simulation and role-play as first responders in emergencies. The results demonstrated a significant improvement in the knowledge of 40 participating students. The average pre-test score was 61, which markedly increased to 93 in the post-test. Statistical analysis confirmed a highly significant difference between pre- and post-intervention scores. Visual and hands-on methods proved highly effective, even in a cross-cultural context, highlighting that empathy and the willingness to help are universal values.